2015
DOI: 10.1148/radiol.14144050
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial CT Perfusion Imaging and SPECT for the Diagnosis of Coronary Artery Disease: A Head-to-Head Comparison from the CORE320 Multicenter Diagnostic Performance Study

Abstract: Figure 1: Receiver operating characteristic curves for myocardial CT perfusion imaging (CTP) and SPECT in, A, all patients and, B, only the patients who underwent pharmacologic stress SPECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Accordingly, a prospective multicenter international trial, the CORE 320 study (n=381), has demonstrated that static CTP imaging has a superior diagnostic accuracy respect to SPECT in detecting obstructive coronary stenosis (≥50%) as compared with ICA (47). The higher sensitivity of CTP imaging was driven in part by its higher sensitivity in the detection of left main and multivessel CAD (47). The difference in diagnostic accuracy may be attributable to the superior spatial resolution of CTP respect to SPECT in the order of submillimeter, which allows detection of subtler subendocardial perfusion defects (47).…”
Section: Ctp Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a prospective multicenter international trial, the CORE 320 study (n=381), has demonstrated that static CTP imaging has a superior diagnostic accuracy respect to SPECT in detecting obstructive coronary stenosis (≥50%) as compared with ICA (47). The higher sensitivity of CTP imaging was driven in part by its higher sensitivity in the detection of left main and multivessel CAD (47). The difference in diagnostic accuracy may be attributable to the superior spatial resolution of CTP respect to SPECT in the order of submillimeter, which allows detection of subtler subendocardial perfusion defects (47).…”
Section: Ctp Imagingmentioning
confidence: 99%
“…The higher sensitivity of CTP imaging was driven in part by its higher sensitivity in the detection of left main and multivessel CAD (47). The difference in diagnostic accuracy may be attributable to the superior spatial resolution of CTP respect to SPECT in the order of submillimeter, which allows detection of subtler subendocardial perfusion defects (47). Another explanation may be the more favorable extraction characteristics of the iodinated contrast material respect to Technetium-based tracers that are susceptible to the roll-off phenomenon, allowing for a linear relationship between CT-derived metrics and MBF (47).…”
Section: Ctp Imagingmentioning
confidence: 99%
“…Cury et al [10] showed in a multicentre study that regadenoson CT-MPI was in good agreement with SPECT for detecting reversible ischaemia. Results from a sub-analysis of the CORE320 (Combined Non-invasive Coronary Angiography and Myocardial Perfusion Imaging Using 320 Detector Computed Tomography) study [11] demonstrated superior diagnostic accuracy of CT-MPI compared to SPECT for predicting obstructive CAD on ICA. Nevertheless, ICA is a suboptimal test to establish the hemodynamic severity of significant stenosis [12].…”
Section: The Role Of Ct-myocardial Perfusion Imaging (Mpi) In Obstrucmentioning
confidence: 99%
“…George RT et al 14 recently demonstrated the overall better sensitivity of adenosine stress myocardial CT perfusion imaging when directly compared to scintigraphic stress myocardial perfusion imaging in the diagnosis of anatomical coronary stenosis defined as C50% by invasive quantitative coronary angiography. The data, however, showed that stress CT perfusion imaging has lower positive predictive values and lower specificities at each coronary territory due to false positive results.…”
Section: See Related Article Pp 1253-1262mentioning
confidence: 99%